2023
DOI: 10.1051/0004-6361/202346981
|View full text |Cite
|
Sign up to set email alerts
|

An extremely metal-poor star complex in the reionization era: Approaching Population III stars with JWST

E. Vanzella,
F. Loiacono,
P. Bergamini
et al.

Abstract: We present JWST/Near Infrared Spectrograph (NIRSpec) integral field spectroscopy (IFS) of a lensed Population III candidate stellar complex (dubbed Lensed And Pristine 1, LAP1), with a lensing-corrected stellar mass of ≲104 M⊙ and an absolute luminosity of MUV > −11.2 (mUV > 35.6), confirmed at redshift 6.639 ± 0.004. The system is strongly amplified (μ ≳ 100) by straddling a critical line of the Hubble Frontier Field galaxy cluster MACS J0416. Although the stellar continuum is currently not detected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…These kinds of effects only matter at very low SFR (∼0.1 M e yr −1 ) at low redshifts, but the bursty nature characterizing many high-z galaxies may still produce a stochastic sampling of the star-forming units within a galaxy (Vikaeus et al 2020;Pallottini & Ferrara 2023). This, in turn, can have important implications for the estimation of metallicities in low-SFR galaxies at high redshifts (e.g., Vanzella et al 2023).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…These kinds of effects only matter at very low SFR (∼0.1 M e yr −1 ) at low redshifts, but the bursty nature characterizing many high-z galaxies may still produce a stochastic sampling of the star-forming units within a galaxy (Vikaeus et al 2020;Pallottini & Ferrara 2023). This, in turn, can have important implications for the estimation of metallicities in low-SFR galaxies at high redshifts (e.g., Vanzella et al 2023).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Through the robust determination of oxygen abundance, our data reveal the distribution of early galaxies in the massmetallicity plane. Despite probing a wide range of both redshift and stellar mass, our galaxies turn out to be moderately enriched in metallicity, Recently, Vanzella et al (2023) reported an upper limit of ( ) log O H +12 < 6.3 on a low-mass star complex (10 4 M e ), through calibrated strong line methods. The system is a part of lensed arcs strongly amplified by the foreground galaxy cluster.…”
Section: Toward the Identification Of Population III Galaxiesmentioning
confidence: 92%

Jades

Maiolino,
Übler,
Perna
et al. 2024
A&A